2011
DOI: 10.2147/ijicmr.s16320
|View full text |Cite
|
Sign up to set email alerts
|

IL-6-induced pathophysiology during pre-eclampsia: potential therapeutic role for magnesium sulfate?

Abstract: Pre-eclampsia is defined as new onset hypertension with proteinuria during pregnancy. Pre-eclampsia is also characterized by endothelial cell activation and dysfunction and intrauterine growth restriction. Preeclamptic women display a chronic inflammatory response characterized by elevated inflammatory cytokines, circulating monocytes, neutrophils, and T and B lymphocytes secreting autoantibodies that activate the angiotensin II type I receptor (AT1-AA). Although the pathophysiology of pre-eclampsia is becomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 47 publications
3
52
0
3
Order By: Relevance
“…31,32 Hence, our findings that hypoxic treatment of the dual placental perfusion system produces significantly higher levels of TNF-a and IFN-g closely parallel the in vivo response in preeclampsia. Furthermore, both IL-6 and IL-8 are found to be significantly increased in preeclampsia, 33,34 and both these pro-inflammatory cytokines were also secreted at a significantly increased rate under hypoxic treatment of the dual placental perfusion system compared with the normoxic group. As there are very few maternal lymphatic cells present in this system, this response to hypoxia most likely originates from the placental trophoblast.…”
Section: Discussionmentioning
confidence: 91%
“…31,32 Hence, our findings that hypoxic treatment of the dual placental perfusion system produces significantly higher levels of TNF-a and IFN-g closely parallel the in vivo response in preeclampsia. Furthermore, both IL-6 and IL-8 are found to be significantly increased in preeclampsia, 33,34 and both these pro-inflammatory cytokines were also secreted at a significantly increased rate under hypoxic treatment of the dual placental perfusion system compared with the normoxic group. As there are very few maternal lymphatic cells present in this system, this response to hypoxia most likely originates from the placental trophoblast.…”
Section: Discussionmentioning
confidence: 91%
“…Th e study investigated the serum values of hs-CRP and IL-6 in the fi rst trimester of pregnancy (weeks [10][11][12][13][14] and in the second trimester of pregnancy (weeks [20][21][22][23][24]. Th e samples were analyzed according to the following study protocol: 3 ml blood were collected on anticoagulant, the plasma was separated by centrifugation for 15 min at 1000 xg.…”
Section: Methodsmentioning
confidence: 99%
“…IL-6 is a multifunctional proinfl ammatory cytokine, produced by vascular endothelial cells, the placenta and leukocytes, with a decisive role in infl ammatory response and the control of T cell diff erentiation in adaptive immunity. IL-6 is also involved in trophoblast proli-feration and invasion and in oxidative stress, being the key circulating marker of endothelial dysfunction [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, much obstetric research has focused on identifying components of the immune system that are activated and play a role in the pathophysiology of preeclampsia. We now know that preeclampsia is associated with elevated inflammatory cytokines, activation of T lymphocytes, and B lymphocyte secreting antibodies that activate receptors that are important in regulating sodium and water homeostasis, such as the angiotensin II type I receptor (9,14,15,26,29).Our laboratory recently reported that placental ischemia (RUPP) increases circulating CD4 ϩ T cells that secrete significantly more tumor necrosis factor-␣ (TNF-␣) and the antiangiogenic factor soluble fms-like tyrosine kinase-1 (sFlt-1) compared with normal pregnant (NP) rats (29). In addition, adoptive transfer of CD4 ϩ T cells from RUPP rats into NP rats increased blood pressure and is associated with an increase in inflammatory cytokines, TNF-␣, interleukin-6, interleukin-17, and sFlt-1, similar to that seen with the RUPP model (29).…”
mentioning
confidence: 99%
“…In recent years, much obstetric research has focused on identifying components of the immune system that are activated and play a role in the pathophysiology of preeclampsia. We now know that preeclampsia is associated with elevated inflammatory cytokines, activation of T lymphocytes, and B lymphocyte secreting antibodies that activate receptors that are important in regulating sodium and water homeostasis, such as the angiotensin II type I receptor (9,14,15,26,29).…”
mentioning
confidence: 99%